Decreased plasma fibrinolysis in patients with rheumatoid arthritis. Issue 6 (December 1984) - Belch, J J; McArdle, B; Madhok, R; McLaughlin, K; Capell, H A; Forbes, C D; Sturrock, R D
Abstract : We have investigated the fibrinolytic status of 56 patients with rheumatoid arthritis (RA). Plasma fibrinogen and plasminogen were significantly elevated. Levels of these two substrates, along with alpha 2 macroglobulin and antithrombin III correlated with disease activity. Plasminogen activator (PA) activity was decreased in patients with severe disease. Twelve patients were given stanozolol, a fibrinolytic enhancing agent, for two months as a test for endothelial production of plasminogen activator. This caused a significant increase in blood plasminogen and PA activity. Five patients received a two-week course of stanozolol with joint aspiration before and after. Joint plasminogen levels were increased. We suggest that inadequate fibrinolysis occurs in RA, and that this may contribute to some of the pathological features of the disease. It is possible to stimulate both blood and joint fibrinolysis by stanozolol. A more prolonged increase in plasminogen activator activity might decrease joint fibrin deposition, and stanozolol should be investigated as a therapeutic agent in RA.